El partido aprista cubano : 1933-1937 - Anderle, Ádám (Acta Hispanica, 2012)
This study is the reinterpretation of a previous study, published in 1975 by the same author, in which he presented the political fights between the Cuban communists (PCC) and Apristas in the 1930s. This research is based on archival sources, party brochures (folletos, volantes) and contemporary printed materials. The study mitten in the 1970s accepted the official communist standpoint and as a result showed a strongly negative, anti-communist image of the Cuban Aprista Tarty (PAC) describing it as a party which hindered the Cuban revolutionary movement and was in favour of American interests. After the publication of the study in Caracas (1978) various Cuban PAC leaders expressed their criticism against it. As a result, the author started his research over. He had the opportunity to look into documents in a few private archives in Havana, enriched his printed material collection, examined the new results in the topic’s literature, and conducted several interviews. Besides this, he critically re-read his previously collected materials (both archival and printed) from the 1970s. In this study the author shows the activity of PAC in an extraordinaty way based-sn his recent research. The study emphasises that the ideas of APRA-PAC share various similarities with the ideas ofJosé Martí who did not think in political pluralism: his concept of democraty meant social and not political democray. PRC founded by him can be understood as a (future) state party as well. The final conclusion of the study is that it was not only Marti’s, but also PAC’s ideas that could have a great role in forming the ideology of Fidel Castro’s Movement.